2010
DOI: 10.1074/jbc.m110.164665
|View full text |Cite
|
Sign up to set email alerts
|

31P Saturation Transfer Spectroscopy Predicts Differential Intracellular Macromolecular Association of ATP and ADP in Skeletal Muscle

Abstract: The kinetics of phosphoryl exchange involving ATP and ADP have been investigated successfully by in vivo 31 P magnetic resonance spectroscopy using magnetization transfer. However, magnetization transfer effects seen on the signals of ATP also could arise from intramolecular cross-relaxation. This relaxation process carries information on the association state of ATP in the cell. To disentangle contributions of chemical exchange and cross-relaxation to magnetization transfer effects seen in 31 P magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 39 publications
4
53
0
Order By: Relevance
“…The nuclear Overhauser effect (NOE), a phenomenon that describes magnetization transfer (MT) through nuclear cross relaxation , is highly useful in a number of applications including in 13 C NMR for improved sensitivity, in solution chemistry for characterizing molecular and protein structures, and in MRI for generating image contrast . Although all of these applications involve magnetization transfer from 1 H polarization, several recent 31 P MT studies demonstrated that in vivo adenosine triphosphate (ATP) may give rise to detectable homonuclear NOE through the 31 P→ 31 P transfer pathway . This is indicated by the observation of β‐ATP signal reduction upon radiofrequency (RF) irradiation at γ‐ATP, a long‐known phenomenon previously either interpreted as 31 P chemical exchange or attributed to discrepancies between pulsing and slow irradiation MT experiments in activating bound pools of phosphate metabolites with very broad lines .…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear Overhauser effect (NOE), a phenomenon that describes magnetization transfer (MT) through nuclear cross relaxation , is highly useful in a number of applications including in 13 C NMR for improved sensitivity, in solution chemistry for characterizing molecular and protein structures, and in MRI for generating image contrast . Although all of these applications involve magnetization transfer from 1 H polarization, several recent 31 P MT studies demonstrated that in vivo adenosine triphosphate (ATP) may give rise to detectable homonuclear NOE through the 31 P→ 31 P transfer pathway . This is indicated by the observation of β‐ATP signal reduction upon radiofrequency (RF) irradiation at γ‐ATP, a long‐known phenomenon previously either interpreted as 31 P chemical exchange or attributed to discrepancies between pulsing and slow irradiation MT experiments in activating bound pools of phosphate metabolites with very broad lines .…”
Section: Introductionmentioning
confidence: 99%
“…Lipid interaction of PCr, leading to specific pools of membrane bound metabolites (see [82]), could also play a role in the organization and efficiency of processes in cellular energy transduction and metabolite channelling, which are largely membrane bound.…”
Section: Discussionmentioning
confidence: 99%
“…The respective 13% and 7% gains in ⌬G MM-CK should have enhanced the functional capacity and kinetic properties of the CK system as a spatial and temporal energy buffer of ATP (Wallimann et al 1992;Aliev et al 2011). Furthermore, because ADP free is only transiently available in vivo (Nabuurs et al 2010) and the magnitude of spikes in ADP free is inversely proportional to [PCr] (Sahlin and Harris 2011), these calculated gains in ⌬G MM-CK must be considered minimum values. Thus it would seem that the major benefit derived from a more uniform distribution of a higher IPP relates to an increase in thermodynamic efficiency of ATP hydrolysis within muscle fibres (Wallimann et al 1992).…”
Section: Thermodynamic Consequences Of Cr Loading On the Ck Systemmentioning
confidence: 99%
“…The creatine-induced increase in the IPP appears to have resulted from the integration of 3 intracellular systems. (i) Sequential reactions catalysed by the near-equilibrium enzymes CK (Cr 0 + ATP 4-¡ PCr 2-+ ADP 3-+ H + ) and AK (2ADP 3-¡ ATP 4-+ AMP 2-) (Golding et al 1995;Nabuurs et al 2010) should have ensured removal of cytosolic ADP free ; further reductions in available ADP free (Fig. 3C) most likely resulted from low-affinity binding of ADP to soluble proteins, which is known to increase in response to training (Sahlin and Harris 2011).…”
Section: Cr Loading Increases Pcr Accretion and The Ippmentioning
confidence: 99%